Evaluation of the clinical nurse career path system in Indonesian Hospitals: Identifying areas for improvement and development - Firman, Firman; Erfina, Erfina; Saleh, Ariyanti (Faculty of Nursing Universitas Padjadjaran, 2024)
Background: The clinical nurse career path system significantly impacts nurses' professional growth, job satisfaction, and service quality. Evaluating its effectiveness is vital for enhancing human resource management. Purpose: This study aimed to evaluate the nursing career path in Indonesia, identifying areas for improvement and development. Method: This study used a mixed-methods approach with nine participants and 339 samples. Surveys targeted clinical nurses, while interviews involved nursing management. Data was analyzed using descriptive statistics and thematic analysis. Results: Managerial experiences revealed three themes: (1) implementation of the nurse career path as a mandatory accreditation process, (2) challenges in the implementation of the nurse career path, and (3) expectations for career path implementation. The process evaluation pinpointed areas for improvement, including organizing, internship programs, Continuous Professional Development (CPD), and career advancement. In product evaluation, 80.8% of nurses had good perceptions, with a 77% job satisfaction rate. Analysis showed a positive correlation between perception and job satisfaction (P < 0.001). Conclusion: The clinical nurse career path in hospitals requires more attention, especially in areas such as human resources, which are not yet full-time, and leadership policies regarding rewards, regulations, and nurse placement in the implementation of career paths related to organizing, internship programs, CPD, and career advancement. Enhancing these aspects is vital for boosting nurses' job satisfaction and improving service quality and patient care.